Rendimiento productivo y calidad de huevo en gallinas ponedoras alimentadas con torta de palmiste (Elaeis guineensis) y enzimas β-glucanasa y xilanasa - Cadillo C., José (2019)
The aim of this experiment was to evaluate the effect of three levels of palm kernel cake (0, 3 and 6%) and the inclusion of two levels of enzymes β-glucanase and xylanase (0 and 0.05%) on the productive performance and quality of eggs in hens. Laying hens of the Hy-Line Brown line (n=216) of 46 weeks of age were used and distributed in a completely randomized block design with a factorial arrangement of 3x2. The experiment lasted 12 weeks. The inclusion of 3% palm kernel cake without enzyme supplementation (T3) significantly improved (p<0.05) the mean egg weight compared to the control treatment (T1). There were no significant differences between treatments with respect to initial and final weight, body weight gain, feed intake, feed conversion, egg production, egg mass, yolk pigmentation and yolk height, shell thickness, egg white height and Haugh units, as well as of energy, protein, lysine and methionine + cystine consumption.